Topical Issues of Polypragmasy in Pediatric Practice - Khalmuratova, F. (Asian Pacific Journal of Environment and Cancer, 2021)
Summary: The problem of polypragmasy remains acute in pediatric practice due to the development of the pharmaceutical industry. Indeed, children are often simultaneously prescribed unreasonable treatment that includes many drugs, which in turn cause many negative consequences for the vulnerable child’s body to improve the effectiveness of treatment. Objective: was to develop the basic principles of rationalization of pharmacotherapy in pediatric practice, taking into account the experience of scientists from foreign countries. Results: of the literature analysis showed that more than 20% of medicines used in pediatrics were poorly justified, often having an increased risk of drug complications associated with their interaction; polypragmasy in pediatric practice was much more frequently observed in inpatient departments, especially in cases with prolonged hospitalization; significant economic damage to the state was caused. Conclusion: the main principles of rationalizing pharmacotherapy in pediatric practice and recommendations have been presented to practitioners interested in pediatric drug therapy.